The Effectiveness of Several Plants as Anesthetics in the Wet Transport System for Oreochromis niloticus Tilapia Fry - Fani Fariedah; Qurrota A'yunin; Soko Nuswantoro; Althov NRH (Life Science, 2025)
Tilapia (Oreochromis niloticus) is a highly valuable aquaculture species, yet handling and transportation processes often induce stress that can reduce survival. Anesthetics are commonly used to minimize stress, but synthetic agents may leave residues and potentially harm both fish and consumers. Therefore, natural plant-based anesthetics are increasingly explored as safer alternatives. This study aimed to evaluate the effectiveness of galangal (Alpinia galanga), bandotan (Ageratum conyzoides), and frangipani flower (Plumeria acuminata) extracts as natural anesthetic agents for tilapia fry during transport. The experiment used a completely randomized design with three treatments and five replications. Tilapia fry (3–5 cm) were exposed for six hours to plant extracts at predetermined doses. Measured parameters included induction time, recovery time, and survival rate. Data were analyzed using ANOVA followed by Tukey’s test. The results indicated significant differences among treatments. Galangal extract produced the fastest induction (3.9 minutes), quickest recovery (5.5 minutes), and highest survival rate (99.6%). Bandotan extract showed moderate performance, while frangipani flower extract produced the slowest induction, longest recovery, and lowest survival (82%). Overall, galangal extract proved to be the most effective and safest natural anesthetic. The study demonstrates that plant-based anesthetics can reduce transport-related stress without leaving harmful residues, offering practical benefits for sustainable aquaculture, especially in wet transport systems.